Nutrition for Musculoskeletal Health (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The maintenance of optimal musculoskeletal health is increasingly recognized as a key element for promoting overall health and fostering independent living in advanced age. Growing evidence indicates that nutrition, together with an active lifestyle, plays a central role in supporting musculoskeletal health both aging and in the setting of specific disease conditions. This Special Issue of Nutrients, entitled “Nutrition for Musculoskeletal Health”, includes original research and review contributions highlighting the relevance of nutrition to musculoskeletal health during aging and in the context of specific diseases. The overarching theme of the Special Issue is addressed through a multidisciplinary set of articles embracing clinical, basic science, and translational studies.